A Cultural Psychological Model of Cross-National Variation in Gender Gaps in STEM Participation. (November 2020) - Soylu Yalcinkaya, Nur; Adams, Glenn
Gender gaps in Science, Technology, Engineering, and Mathematics (STEM) participation are larger in societies where women have greater freedom of choice. We provide a cultural psychological model to explain this pattern. We consider how individualistic/post-materialistic cultural patterns in WEIRD (Western, Educated, Industrial, Rich, and Democratic) settings foster a self-expressive construction of academic choice, whereby affirming femininity/masculinity and ensuring identity fit become primary goals. Striving to fulfill these goals can lead men toward, and women away from, STEM pursuit, resulting in a large gender gap. In Majority World settings, on the contrary, collectivistic/materialistic cultural patterns foster a security-oriented construction, whereby achieving financial security and fulfilling relational expectations become primary goals of academic choice. These goals can lead both women and men toward secure and lucrative fields like STEM, resulting in a smaller gender gap. Finally, gender gaps in STEM participation feed back into the STEM=male stereotype. We discuss the implications of our model for research and theory, and intervention and policy.